Removal of Chromium(III) Ions by Raw and Activated Carbon Derived from Mandarin Peel - Alshabanat, Mashael (Asian Journal of Chemistry, 2018)
Removal of chromium(III) ions was investigated using raw mandarin peel and activated carbon derived from it. The percentage removal of Cr3+ ions was studied as a function of initial concentration of the heavy metal solution, pH and separation time. The results showed that the maximum percentage removal of chromium(III) of 67 % at 0.1 × 10-3 mg/L by raw mandarin peel sample and 80 % at 0.025 × 10-3 mg/L by activated carbon sample, 73 % in alkaline media and 60 % in natural media by activated carbon and raw mandarin peel, respectively; and reached to 67 and 81 % after 30 min of separation time by raw mandarin peel and activated carbon, respectively. Further, the observation also showed an acceptable efficiency for the removal of Cr3+ ions by the both adsorbents, particularly by activated carbon when compared to raw mandarin peel sample.